(untitled) (Shanti Journal, 2023)
This article explores the socio-economic adjustment of rural migrants in the cities of Kathmandu Valley. This study was conducted among Sampang Rai migrants and utilizes the network theory of migration. Information was gathered through questionnaire using KoBoToolbox, in-depth interviews, and observation in the study areas. Sampang Rais migrate to the Kathmandu Valley to get an education, find better work, experience city life, help their families, get medical treatment, and learn new skills. The already established and available networks facilitate the selection of migration destinations and socio-economic adjustment in Kathmandu Valley. Friends, families, earlier migrants, and institutions assisted migrants to adjust socially and economically in the destination areas by providing information, physical resources, material resources, and sociocultural support. Sampang Rai migrants also made efforts to diversify their livelihood, keep strong connections with friends and families, join religious communities, learn new skills, exchange labour and encourage one another while they go through the process of socio-economic adjustment.